A VECTOR ERROR CORRECTION MODEL APPROACH IN EXPLAINING THE RELATIONSHIP BETWEEN FOREIGN DEBT ON ECONOMIC GROWTH IN INDONESIA - Antoni, Antoni (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This article examines the relationship between trade opening and government spending on economic growth. The method used vector error correction model (VECM). While the integration test uses the Johansen method. The data used in this study date are from 1985-2018. Empirical results indicate an insignificant long-term relationship between economic growth and foreign debt, trade openes and government spending. This causes a significant negative relationship between foreign debt and government spending and short-term economic growth. While the trade openes and consumer spending variables did not significantly influence economic growth. The policy implications of this research are very important, in the formulation of macroeconomic policies to achieve macroeconomic stability and thus contribute to the development of trade opening, government spending and foreign debt. Keywords: Foreign Debt, Trade Openes, Government Expenditures, Growth, VECM JEL Classification Code : C32, G20, H54, L74, O4